2018
DOI: 10.1016/j.neuropharm.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A single cocaine administration alters dendritic spine morphology and impairs glutamate receptor synaptic retention in the medial prefrontal cortex of adolescent rats

Abstract: The brain is still maturing during adolescence and interfering with such a vulnerable period may lead to structural and functional consequences. We investigated the effect of a single cocaine exposure on dendritic spine structure and glutamate dynamics in the medial prefrontal cortex (mPFC) of adolescent rats 7 days after a single cocaine administration. We found a reduced number of dendritic spines, suggesting that cocaine lowers the density of dendritic spines in the mPFC of adolescent rats. Since dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Dendritic spines mediate transmission of electrical signals to the neuron. They contain NMDA receptors and AMPA receptors [78]. The dendritic spine geometry is AMPA receptor and NMDA receptor-dependent Ca 2+ signaling currents in dendrites [79–81].…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic spines mediate transmission of electrical signals to the neuron. They contain NMDA receptors and AMPA receptors [78]. The dendritic spine geometry is AMPA receptor and NMDA receptor-dependent Ca 2+ signaling currents in dendrites [79–81].…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic spines, de ned as small protrusions arising from dendrites, are used for communication by excitatory glutamatergic synapses of the CNS. They are remarkably dynamic structures that may undergo adaptive changes following different stimuli [49], and their structural plasticity is thought to underlie memory formation [50]. In this study, we found that LPS treatment signi cantly decreased the densities of dendritic spines and dendritic processes intersections.…”
Section: Discussionmentioning
confidence: 51%
“…Proteins from hippocampal slices were extracted as previously described with minor modifications (Caffino et al., 2018; Fumagalli et al, 2008). Briefly, hippocampal slices were homogenized in a teflon‐glass homogenizer in cold 0.32 M sucrose buffer pH 7.4 containing 1 mM HEPES, 1 mM MgCl2, 1 mM NaHCO3 and 0.1 mM PMSF, in presence of commercial cocktails of protease (Roche) and phosphatase (Sigma‐Aldrich) inhibitors and an aliquot of each homogenate was then sonicated.…”
Section: Methodsmentioning
confidence: 99%